МОДЕЛЮВАННЯ ВИДАТКІВ ІНКЛЮЗИВНОГО ВИЩОГО НАВЧАЛЬНОГО ЗАКЛАДУ - Тріпак, Мар'ян Миколайович (Науковий журнал «Світ фінансів», 2018)
Тріпак М. М. Моделювання видатків інклюзивного вищого навчального закладу. Проведено моніторинг кошторисного фінансування Подільського спеціального навчально-реабілітаційного соціально-економічного коледжу у розрізі загального та спеціального фондів. Розроблено власні методологічні аспекти щодо оптимізації структури видатків загального фонду кошторису коледжу в умовах ефективного їх виконання, враховуючи особливості соціально-культурного та оздоровчо-реабілітаційного соціуму. Опрацьовано логічні ланцюжки першочерговості планування відповідних видатків, які покликані позитивно впливати на стан соціального розвитку коледжу. Визначено напрямки економії бюджетних коштів. Трипак М. Н. Моделирование расходов инклюзивного высшего учебного заведения. Проведен мониторинг сметного финансирования Подольского специального учебно-реабилитационного социально-экономического колледжа в разрезе общего и специального фондов. Разработаны собственные методологические аспекты по оптимизации структуры расходов общего фонда сметы колледжа в условиях эффективного их выполнения, учитывая особенности социально-культурного и оздоровительно-реабилитационного социума. Обработаны логические цепочки первоочередности планирования соответствующих расходов, призваны положительно влиять на состояние социального развития колледжа. Определены направления экономии бюджетных средств. Tripak M. Modeling of expenditure of the inclusive higher education institution. Purpose. The logic chains of primary importance in planning of the relevant expenses, which had been called to influence positively to the social development of the college are processed. The directions of budget savings in the college are determined. Methodology of research. The article uses modern general scientific and special methods of economic research, in particular: a systematic approach – when studying the connections between phenomena and processes of analysis of the financial state of the inclusive institution; statistical analysis – in determining the dynamics, structure of financial resources of the inclusive institution of higher education in the context of general and special funds; dialectical and abstract-logical – when conducting theoretical generalizations and forming conclusions. Results. The author’s own methodological aspects are developed with the help of mathematical modeling in relation to optimization of the structure of the college general fund budget expenditures in conditions of their effective implementation, taking into account the features of socio-cultural, health and rehabilitation society. Therefore, for the effective redistribution of the funds of the general fund of the college, we use a mathematical model, which defines the main factors of the activity of the higher education institution in conditions of socio-cultural and recreational rehabilitation. As outcome indicators, the frequency of "desirable and undesirable" factors that characterize the state of functional classification of cost estimates, as well as their correlation to the amount involved in expenditure estimates, that is, intensity indicators are offered. Thus, the logic chains of the general fund structure are determined, which should positively influence on the state of social development of the inclusive higher education institution. Conclusions. Taking into account the above-mentioned methodology, about 7 thousand UAH of funds of the general fund of the college budget are saved. The same marginal cost savings can be achieved through the support of funding for educational, club activities work and physical education rehabilitation, which should actively generate a program of the development of social activities of college students.